The function and clinical implication of circular RNAs in lung cancer - Jiang, Xiulin; Duan, Lincan (Frontiers in Oncology, 2022)
Lung cancer is the leading cause of cancer-related death worldwide. Despite the recent advent of promising new targeted therapies, it is still a great challenge to identify the patients at an early stage. Therefore, it is necessary to discover sensible and specific cancer biomarkers for the disease. Circular RNAs are covalently close, endogenous RNAs without 5′ end caps or 3′poly (A) tails. Interestingly, it has been characterized by high stability, abundance, conservation and display cell/tissue/developmental stage-specific expression. Numerous studies have confirmed that circRNAs act as microRNA (miRNA) sponges, RNA-binding protein-and transcriptional regulators, some circRNAs even act as translation templates participated in multiple pathophysiological processes. Growing evidence have confirmed that circRNAs involved in the pathogenesis of lung cancers through regulated the proliferation and invasion, cell cycle, cell autophagy, cell apoptosis, stemness, chemotherapy resistance and tumour microenvironment. Moreover, circRNAs have emerged as potential biomarkers for lung cancer diagnosis and prognosis and targets for developing new treatments. In this review, we will also summarize recent progresses in the biogenesis, biological functions, potential mechanisms and clinical applications of circRNAs for lung cancer.